Mobile Application Development with Android - Rajesh Keshavrao Deshmukh; Shilpa Markandey; Pooja Sahu (Institute of Advanced Engineering and Science, 2018)
The Android is mobile platform. It is an open source and free operating system application, by Google it is developed and maintained. It was designed essentially for touch screen mobile devices, such as and tablet, computers, smart phones, watch television, cars etc. Android is one of the most widely used mobile OS. Android is a not only operating system but also key applications and middleware. Android is an open source operating system. It is developed by the open handset Alliance, led by Google, and other companies. Those are used to android studio 2.2.3 version and development the mobile application.